2022
DOI: 10.1177/10556656221128436
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Pregnancy Outcomes of Fetuses With Orofacial Cleft: A Retrospective Cohort Study in Two Centres in Hong Kong

Abstract: Objective To evaluate the local incidence of orofacial cleft (OFC) encountered in fetal morphology scan and prenatal diagnosis, genetic etiology of fetuses with or without other structural abnormalities, and their pregnancy outcomes. Design Retrospective cohort study. Setting Two maternal fetal medicine units, tertiary hospitals, Hong Kong. Participants All pregnant women with antenatal diagnosis of fetal OFC between January 2016 and December 2020 (N = 66). Results OFC has an incidence of 0.13% among pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…These syndromic defects are attributed to mutations and deletions that lead to the loss of function of one or more genes 18 . In our cohort, there was a signi cant difference in the detection rate of isolated CL/CP and nonisolated CL/CP (11/33, 33.3% vs. 15/305, 4.9%, p < 0.001), a nding which is similar to previous studies 11 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These syndromic defects are attributed to mutations and deletions that lead to the loss of function of one or more genes 18 . In our cohort, there was a signi cant difference in the detection rate of isolated CL/CP and nonisolated CL/CP (11/33, 33.3% vs. 15/305, 4.9%, p < 0.001), a nding which is similar to previous studies 11 .…”
Section: Discussionsupporting
confidence: 91%
“…According to report that CMA identi ed clinically signi cant genomic alterations in approximately 6% of fetuses exhibiting abnormal ultrasound and with normal karyotype 9 . While there have been several research publications on prenatal diagnosis of fetal CL/CP utilizing CMA 10,11 , the comprehensive assessment of the speci c information about fetuses with CL/CP through CMA is currently limited.…”
Section: Introductionmentioning
confidence: 99%
“…Burnell et al reported a live birth rate of 84.5% (82/97) and 84.4% (65/77) long-term favorable outcomes without complex disorders in isolated CL/P cases. Li et al found a live birth rate of 43.9% (29/66) and 87.5% (21/24) had good long-term outcomes without any detectable pathogenic genetic abnormalities ( Burnell et al, 2014 ; Li et al, 2022 ). In our study, the live birth rate was 48.6% (52/107), similar to Li’s study.…”
Section: Discussionmentioning
confidence: 99%